Efektivitas Kombinasi Pemberian Edukasi Kesehatan, Relaksasi Napas Dalam dan Relaksasi Otot Progresif terhadap Kualitas Tidur Penderita Hipertensi - Nurwahidah, Nurwahidah; Susila, Wahyu Dini Candra; Bakar, Abu; Harmayetty, Harmayetty; Metrikayanto, Wahyu Dini (Universitas Tribhuwana Tunggadewi, 2023)
Hypertension stands as a perilous non-communicable disease, often leading to emotional instability among affected individuals. Symptoms like irritability, sleeplessness, and stress are commonly experienced by those with hypertension. Sleep quality is notably disrupted, with patients frequently experiencing discomfort and worry, often manifested as headaches, leading to disturbed sleep patterns. A multi-pronged approach is crucial for optimal results. Non-pharmacological interventions, combining health education with stress management techniques like progressive muscle relaxation (PMR) and deep breathing exercises, prove beneficial. This study aimed to evaluate the effectiveness of this combined approach on the sleep quality of hypertensive patients, utilizing a quantitative pre-experimental one-group pretest-posttest research design. The non-probability sampling technique employed accidental sampling, involving 17 hypertensive patients meeting specific criteria. The Wilcoxon Signed Ranks test yielded a significant result (p-value) of 0.000 ≤ 0.05. The combined intervention of health education, deep breath relaxation, and progressive muscle relaxation exhibited a positive impact on improving sleep quality among hypertensive patients. Further qualitative research is warranted to explore the experiences of hypertensive patients engaging in routine deep breath relaxation and progressive muscle relaxation therapies.